Psychometric properties of the Chinese version of the nurses' attitudes towards communication with the patient scale among Chinese nurses - Meng Yue; Qiaoling Chen; Ying Liu; Rui Cheng; Dengfen Zeng (BMC, 2024)
Abstract Background Nurses' attitudes towards communication with patients influence the effectiveness of communication, which could reduce patients' negative emotions and improve their adherence to medication and treatment. The aim of this study was to develop a Chinese version of the nurses' attitudes towards communication with the patient (ACO) scale and examined its validity and reliability. Methods The Chinese version ACO scale was generated using the translation-backward translation method and cross-cultural adaption.The psychometric properties of the scale, including item-to-total correlations, discriminative validity, content validity, structural validity, convergent validity, internal consistency reliability and test-retest reliability, were evaluated. Data were collected from a convenience sample of 610 clinical nurses from four hospitals and were analyzed using both exploratory factor analysis and second-order confirmatory factor analysis. Result The reliability was demonstrated with item-to-total correlations of greater than 0.40, Cronbach's alpha of 0.946 and intraclass correlation coefficients of 0.879. Content validity was acceptable and discriminative validity showed a significant discriminative ability. Exploratory and confirmatory factor analyses revealed a three-factor model. Convergent validity was confirmed by a moderate relation with a measure for nurses' empathy (r = 0.375, P<0.01).The test-retest reliability was satisfactory within a 2-week interval. Conclusion The ACO is a reliable and valid instrument to assess nurses' attitudes towards communication with patient in Chinese hospitals.